Enhanced Arterial Spin Labeling Magnetic Resonance Imaging of Cerebral Blood Flow of the Anterior and Posterior Circulations in Patients With Intracranial Atherosclerotic Stenosis - Yu, Hongwei; Li, Yangchen; Feng, Yibo; Zhang, Linwei; Yao, Zeshan; Liu, Zunjing; Gao, Wenwen; Chen, Yue; Xie, Sheng (Frontiers in Neuroscience, 2022)
This study analysed the differences in the mCBF and ATT of the anterior and posterior circulations between patients with ICAS and controls. Also investigated the effect of ATT on mCBF measure in the two groups and the relationship between the blood flow velocity of the carotid/vertebral arteries and the ATT of the anterior and posterior circulations. 32 patients with ICAS were enrolled. 17 had severe cerebral arterial stenosis in the anterior circulation and 15 in the posterior circulation. 32healthy subjects were enrolled. MRA and eASL and CDU were performed. The t-test was used to compare mCBF and ATT of the anterior and the posterior circulation between both groups. Analysis of covariance was used to compare the effect of ATT on mCBF. The blood flow velocity of the internal carotid/vertebral arteries were compared by the t-test. Multiple linear regression analysis was used to analyse the effects of the mPSV and mEDV of the internal carotid artery on the ATT of the anterior circulation, and on the ATT of the posterior circulation. The mCBF of the anterior and posterior circulations in the study were lower than those of the control, while the ATT in the study group were longer than those of the control group. In the control and study group, except for the ATT in the insula, ATT had an effect on the mCBF over the brain, both in the anterior and posterior circulations. However, no group effect was found in the occipital lobes and cerebellum. The blood flow velocity of the internal carotid/vertebral arteries are not statistically different between twe groups. Also, the mPSV and mEDV of the internal carotid artery and the vertebral artery had no effect on the anterior and posterior circulations in the control group. The mEDV of the ICA and the VA in the study group had negative correlations with the ATT of the anterior and posterior circulations. There was a relationship between the ATT and mCBF over the brain in the healthy people and in the patients with ICAS. The maintainence of extracranial blood flow is of great significance in the preservation of intracranial hemodynamic